Անկանխիկ դրամաշրջանառության ժամանակագրական փոփոխությունների վերլուծությունը ՀՀ-ում - Ռոբերտ Սոսի Քոչարյան (ՀՀ ԳԱԱ հրատ.)
Денежный оборот имеет большое значение для любой страны, включая Армению, особенно в деле регулирования денежнокредитно политики. Существует два типа денежного обращения: первый -это движение наличных денег, то есть обращение банкнот и монет, а второй -безналичный оборот. В статье представлен анализ динамических изменений безналичного оборота Армении на основе статистических данных. Обзор обобщен экономическими комментариями и выводами.Money in circulation is of a great importance to any country,including Armenia, namely, in the process of regulating the monetary policy. Two types of money in circulation could be distinguished: first, cash in circulation, that is currency and coins in circulation; and second, non-cash in circulation. The article presents an analysis of the dynamics on Armenia's non-cash in circulation based on the statistical data. The study provides respective economic interpretations and conclusions.
Keywords: Հասարակական գիտություններ; Տնտեսագիտության տեսություն; Ֆինանսներ